Global experimentalist governance - Burca, Grainee De; Sabel, Charles; Keohane, Robert O. (2014)
This article outlines the concept of Global Experimentalist Governance (GXG). GXG is an institutionalized transnational process of participatory and multilevel problem solving, in which particular problems, and the means of addressing them, are framed in an open-ended way, and subjected to periodic revision by various forms of peer review in light of locally generated knowledge. GXG differs from other forms of international organization and transnational governance, and is emerging in various issue areas. The Montreal Protocol on ozone-depleting substances is used to illustrate how GXG functions. The conditions for the emergence of GXG are specified, as well as some of its possible benefits. - Reproduced.
Keywords: Public administration